Media and cultural studies. keyworks - DURHAM, Meenakshi Gigi (Blackwell Publishing, 2006)
Media and Cultural Studies: KeyWorks is a comprehensive anthology of the most significant and frequently cited theoretical readings pertaining to critical approaches to media culture and communications. Spanning the gamut from the writings of Antonio Gramsci and the Frankfurt School to recent essays on identity, race, gender, and the postmodern turn, this book offers a range of core texts that have never before been collected into a single volume. The burgeoning popularity of media and cultural studies in a variety of academic disciplines makes this book an indispensable scholarly and pedagogical tool, particularly because of the in–depth analytical overview of critical media studies provided in the editors′ introduction, as well as the annotations for each section of the book. The scope and depth of the volume fill a longstanding gap in the literature in this area; the book will find a permanent place on the bookshelves of scholars in this field, as well as being required reading for students in cultural studies, media studies, sociology, and related disciplines.